2017
DOI: 10.1051/parasite/2017010
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence ofToxoplasma gondiiinfection in domestic cats in central China

Abstract: To investigate the seroprevalence of Toxoplasma gondii infection in domestic cats in central China, 843 serum samples were collected in Henan province between March 2015 and May 2016 and tested for IgG antibodies against T. gondii using the enzyme-linked immunosorbent assay (ELISA). The overall seroprevalence of T. gondii was 21% (178/843). No significant difference was observed based on the sex of cats (p > 0.05). Significantly higher seroprevalence (p < 0.05) was observed in mixed-breed cats (24%) compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…The seropositive rate of T. gondii in children living in rural areas was significantly higher than that in urban areas, which was consistent with other reports [4,19]. Our previous research results confirmed that the seroprevalence of T. gondii in rural cats (29.26%) was significantly higher than in urban cats (16.35%) in Henan province [25]. This may lead to increased environmental contamination by T. gondii oocysts in rural areas, which in turn increases the risk of exposure to T. gondii in children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The seropositive rate of T. gondii in children living in rural areas was significantly higher than that in urban areas, which was consistent with other reports [4,19]. Our previous research results confirmed that the seroprevalence of T. gondii in rural cats (29.26%) was significantly higher than in urban cats (16.35%) in Henan province [25]. This may lead to increased environmental contamination by T. gondii oocysts in rural areas, which in turn increases the risk of exposure to T. gondii in children.…”
Section: Discussionsupporting
confidence: 91%
“…Felids act as the only final host of T. gondii and thus play an essential role in transmitting this parasite. Infected cats are considered to be a potential threat to public health because they can excrete environmentally resistant oocysts in their feces [25]. In mainland China, seroprevalence of T. gondii infection in cats ranged from 3.9% to 79.4% [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because these foods had a higher level of contamination of T. gondii oocysts or E. cuniculi spores than feed or mixed food. Cats play an essential role in T. gondii spreading since they are the final hosts and shed oocysts into the environment [ 11 , 20 ]. In this study, the presence of cats on rabbit farms was confirmed as one of the risk factors for occurrence of T. gondii infection among rabbits, which accorded with findings in previous literature reports [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence varied by area of the island (5.1–19.6%). In epidemiological studies in other countries, the T. gondii antibody seroprevalence among cats in rural areas has tended to be higher than that in urban cats [ 6 , 10 ]. In our present study, there was a similar tendency.…”
mentioning
confidence: 99%